Identification of a mutation causing a defective spindle assembly checkpoint in high ethyl caproate-producing sake yeast strain K1801. Issue 8 (2nd August 2016) - Goshima, Tetsuya; Nakamura, Ryo; Kume, Kazunori; Okada, Hiroki; Ichikawa, Eri; Tamura, Hiroyasu; Hasuda, Hirokazu; Inahashi, Masaaki; Okazaki, Naoto; Akao, Takeshi; Shimoi, Hitoshi; Mizunuma, Masaki; et al.
Abstract: In high-quality sake brewing, the cerulenin-resistant sake yeast K1801 with high ethyl caproate-producing ability has been used widely; however, K1801 has a defective spindle assembly checkpoint (SAC). To identify the mutation causing this defect, we first searched for sake yeasts with a SAC-defect like K1801 and found that K13 had such a defect. Then, we searched for a common SNP in only K1801 and K13 by examining 15 checkpoint-related genes in 23 sake yeasts, and found 1 mutation, R48P of Cdc55, the PP2A regulatory B subunit that is important for the SAC. Furthermore, we confirmed that the Cdc55-R48P mutation was responsible for the SAC-defect in K1801 by molecular genetic analyses. Morphological analysis indicated that this mutation caused a high cell morphological variation. But this mutation did not affect the excellent brewing properties of K1801. Thus, this mutation is a target for breeding of a new risk-free K1801 with normal checkpoint integrity. Graphical abstract: : K1801 (triploid) having 2 copies of R48P-type cdc55 and 1 copy of R48-type cdc55 showed a defective spindle assembly checkpoint (SAC). Cdc55-R48P is semidominant mutation in the SAC function.